Rhabdomyosarcoma: How Advanced Molecular Methods Are Shaping the Diagnostic and Therapeutic Paradigm. (September 2021) - Giannikopoulos, Petros; Parham, David M
For the past 40 years, progress in rhabdomyosarcoma (RMS) has been focused on understanding its molecular basis and characterizing the mutations that drive its tumorigenesis and progression. Genetic predisposition to RMS has allowed discovery of key genetic pathways and driver mutations. Subclassification of RMS into embryonal (ERMS) and alveolar (ARMS) subtypes has shifted from histology to PAX-FOXO1 fusion status, and new driver mutations have been found in spindle cell RMS. Comprehensive molecular profiling leveraging genome-scale next-generation sequencing (NGS) indicates that the RAS/RAF/PI3K axis is mutated in the majority of ERMS and modulated by downstream effects of PAX-FOXO1 fusions in ARMS. Because of the continued poor outcome of high-risk RMS, a variety of molecular targets have been or are now being tested in current or recent therapy trials. New techniques such as single cell sequencing, spatial multi-omics, and CRISPR/Cas9 genome editing offer potential for further discovery, but a need for clinically annotated specimens persists.